Study the behavior of reinforcement concrete beams externally reinforced with carbon fiber strips - Marwan B.S Alferjani , Rabie A Almardi Amnisi, Khaled Idris Hamad, Heba Ahamed Khalifa, Sajada Khaled Salem (Journal of Pure & Applied Sciences, 2020)
The use of fiber reinforced polymers as an external reinforcement has become one of the alternatives solutions for repairing defect of shear and flexure in reinforced concrete structure. Concrete elements need to be reinforced when their resistance is insufficient as a result of a change in the facility's use or as a result of design or implementation errors. Also, the structural elements may need restoration and repair in cases of lack of tolerance as a result of exposure to various environmental influences or exposure to acts of deliberate sabotage or any other errors that arise from human action. Currently, polymer fibers have found their way for use in civil engineering applications, as external reinforcement has been used to improve the performance of installations such as reinforcing concrete columns by creating a collar on the polymeric fibers, transforming the outer perimeter of the column to increase resistance and ductility, and also used to increase the bending resistance and shear with polymer fibers adhesives on the outside of the beams and roofs. The central polymer fibers are used in the external reinforcement of the installations for the purpose of improving their bending and shear performance relative to the concrete beams by attaching the polymer fibers to the outer surface of the beams. There is a lack of studies that cover shear and bending defects that need to be strengthened in the beams, and therefore more work needs to be done to study the strengthening of the beams, and therefore, to solve this problem there is a need to investigate the effectiveness of the carbon-coated strips externally to strengthen the shear and bending in the beams. In this study, a total of 4 identical rectangular reinforced concrete beams were selected with dimensions of 120x200x1000 mm.